2022
DOI: 10.1057/s41267-022-00581-z
|View full text |Cite
|
Sign up to set email alerts
|

Africa rising: Opportunities for advancing theory on people, institutions, and the nation state in international business

Abstract: Africa is rising, but IB scholars have largely failed to take notice. We argue that this is a missed opportunity. Not only is Africa a dynamic and distinctive region, but its rise presents a number of puzzles for international business (IB) research, with phenomena that seem to challenge fundamental assumptions underlying IB theories. In order to unravel these puzzles and better explain business dynamics on the continent, we contend that there is a need for IB theorizing to place greater emphasis on the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 105 publications
(141 reference statements)
0
9
0
Order By: Relevance
“…These are key to the effective development, growth and sustainability of EMNCs in emerging markets. This combination of both flexibility and resilience, and an ability to improvise in turbulent, institutionally ambiguous—even dysfunctional and weak—regulatory environments in Africa, is supported by the work of Cooke et al (2015), Kamoche and Wood (2022), Munene (1991) and Nachum et al (2022), and has been identified as a fruitful avenue for further research (Cunha et al, 2022).…”
Section: Local Employment Labour Markets and Human Resourcesmentioning
confidence: 95%
See 3 more Smart Citations
“…These are key to the effective development, growth and sustainability of EMNCs in emerging markets. This combination of both flexibility and resilience, and an ability to improvise in turbulent, institutionally ambiguous—even dysfunctional and weak—regulatory environments in Africa, is supported by the work of Cooke et al (2015), Kamoche and Wood (2022), Munene (1991) and Nachum et al (2022), and has been identified as a fruitful avenue for further research (Cunha et al, 2022).…”
Section: Local Employment Labour Markets and Human Resourcesmentioning
confidence: 95%
“…It is estimated that there are some 3 million individuals in the African Indian diaspora living mainly in East and Southeast Africa. Although a relatively small number, it is a community which has had an outsized economic and political influence both domestically and in building ties between African countries and India (Nachum et al, 2022). Some of this diaspora arrived in the nineteenth century from colonial British India as indentured labourers, working on the Kenya-Uganda railway and sugar industry in Kwa-Zulu Natal, South Africa.…”
Section: Socio-historical Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…While IB researchers have been adding to our knowledge of emerging markets, their focus has primarily been on China and India. Africa represents many developing and emerging markets and can provide new insights for the IB field (see, for example, Nachum et al , 2022). Nigeria is the largest economy in Africa, with a population of over 200 million people.…”
Section: Introductionmentioning
confidence: 99%